ArtMaps: interpreting the spatial footprints of artworks - Coughlan, Tim; Carletti, Laura; Giannachi, Gabriella; Benford, Steve; McAuley, Derek; Price, Dominic; Locatelli, Cristina; Sinker, Rebecca; Stack, John (2015)
Creating and utilizing simple links between items and locations in map-based systems has become a mainstream component of modern computing. In this paper, we explore support for ‘art mapping’, an activity that requires consideration of more complex interpretations of spatial relationships as users engage with identifying locations of relevance to artworks. Through a user study of the ArtMaps platform, and an exploratory study with professional artists, we identify diverse interpretations of spatial meaning in relation to art. We find that art mapping highlights potential for more active engagement with art through technology, but challenges existing systems for spatial representation. Through connecting our findings with work on designing for interpretation, and on space and place in HCI, we contribute new understanding of creating engagement through the spatial interpretation of art, and define potential characteristics and uses of holistic ‘footprints’ for artworks.